1
$\begingroup$

Prove that if $ab \equiv cd \pmod{n}$ and $b \equiv d \pmod n$ and $\gcd(b, n) = 1$ then $a \equiv c \pmod n$.

From this we know that $\gcd(d, n) = 1$. I can't derive anything else. Please help. Is there some basic theorem which points to this? Can we cut out $b$ and $d$ in $ab \equiv cd \pmod{n}$ if we know they leave the same residues $\pmod n$?

Thanks.

$\endgroup$
  • 1
    $\begingroup$ The gcd condition implies that $b$ (hence also $d$) is invertible $\endgroup$ – Hagen von Eitzen May 2 '16 at 13:26
  • $\begingroup$ @HagenvonEitzen How do you define invertible? $\endgroup$ – TheRandomGuy May 2 '16 at 13:28
1
$\begingroup$

Lemma. If $xz\equiv yz \pmod{n}$, then $x\equiv y\pmod {\frac{n}{d}}$, where $d=\gcd(n,z)$.

Proof. $n|z(y-x)\implies \frac{n}{d}\big| \frac{z}{d}(y-x)$. Hence, $\gcd(\frac{n}{d},\frac{z}{d})=1$, which implies that $\frac{n}{d}\big|(y-x)$.//

Now, since $\gcd(b,n)=\gcd(d,n)=1$, we can use the above lemma as follows:

$$ \begin{aligned} ab\equiv cd\pmod{n}\text{ and }b\equiv d\pmod {n} &\implies abd\equiv cbd\pmod {n}\\ &\implies ab\equiv cb\pmod {n}\qquad\text{by the lemma}\\ &\implies a\equiv c\pmod{n}\qquad\text{by the lemma}. \end{aligned} $$

$\endgroup$
  • 1
    $\begingroup$ Thanks! ${}{}{}{}{}$ BTW our rep is equal. $\endgroup$ – TheRandomGuy May 2 '16 at 13:40
  • 1
    $\begingroup$ :-) I'm happy!! $\endgroup$ – ervx May 2 '16 at 13:41
2
$\begingroup$

For some reason I think it is fun solving problems like this using Bezout's lemma: since ${\rm gcd}(b,n) = 1$ there exist integers $x$ and $y$ with $$\tag 1 bx + ny = 1.$$ Since $ab \equiv cd \bmod n$ there is an integer $s$ such that $$\tag 2 ab = cd + ns$$ and since $b \equiv d \bmod n$ there is an integer $t$ such that $$\tag 3 b = d + nt.$$

Multiply line (1) by $a$ and $c$ individually to get \begin{align} \tag 4 abx + any &= a \\ \tag 5 bcx + cny &= c.\end{align}

Multiply line (2) by $x$ to get $$\tag 6 abx = cdx + nsx$$ and multiply line (3) by $cx$ to get $$\tag 7 bcx = cdx + cntx.$$ Now subtract (7) from (6) to get $$abx - bcx = n(sx - ntx)$$ and use this result to subtract (5) from (4): $$n(sx - ntx) + n(ay - cy) = a-c.$$ Thus $n$ divides $a-c$ as you wanted.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.